AN ANALYSIS OF DIRECTIVE SPEECH ACTS USED BY NAJWA SHIHAB ON CATATAN NAJWA PODCAST “SUSAHNYA JADI PEREMPUAN” - Romadhona, Ihda Rozfania; Wafa, Hosnol; Tjahyadi, Indra; Andayani, Sri (Program Studi Bahasa Inggris, Universitas Panca Marga, 2024)
The development of podcasts is starting to look brighter every day, with many public figures across the country competing to launch podcasts via YouTube. One of them is a podcast on Najwa Shihab's YouTube channel entitled